Al-free cladding-layer blue laser diodes with a low aspect ratio in far-field beam pattern *Project supported by the National Key R&D Program (Nos. 2017YFB0403100, 2017YFB0403101), the National Natural Science Foundation of China (Nos. 61534007, 61404156, 61522407, 61604168, 61775230), the Key Frontier Scientific Research Program of the Chinese Academy of Sciences (No. QYZDB-SSW-JSC014), the Science and Technology Service Network Initiative of the Chinese Academy of Sciences, the Key R&D Program of Jiangsu Province (No. BE2017079), the Natural Science Foundation of Jiangsu Province (No. BK20160401), and the China Postdoctoral Science Foundation (No. 2016M591944). Project was also supported by the Open Fund of the State Key Laboratory of Luminescence and Applications (No. SKLA-2016-01), the Open Fund of the State Key Laboratory on Integrated Optoelectronics (Nos. IOSKL2016KF04, IOSKL2016KF07), and the Seed Fund from SINANO, CAS (No. Y5AAQ51001). Project also supported technically by Nano Fabrication Facility, Platform for Characterization & Test, Nano-X of SINANO, CAS. (August 2018) - Feng, Meixin; Sun, Qian; Liu, Jianping; Li, Zengcheng; Zhou, Yu; Gao, Hongwei; Zhang, Shuming; Yang, Hui
Abstract: c -plane GaN-based blue laser diodes (LDs) were fabricated with Al-free cladding layers (CLs) and deepened etching depth of mesa structure, so the aspect ratio of the far-field pattern (FFP) of the laser beam can be reduced to as low as 1.7, which is nearly the same as conventional AlGaInP-based red LDs. By using GaN CLs, the radiation angle of the laser beam θ ⊥ is only 10.1° in the direction perpendicular to the junction plane. After forming a deeply etched mesa, the beam divergence angle parallel to the junction plane of FFP, θ //, increases from 4.9° to 5.8°. After using the modified structure, the operation voltage of LD is effectively reduced by 2 V at an injection current of 50 mA, but the threshold current value increases. The etching damage may be one of the main reasons responsible for the increase of the threshold current.